Déchets ménagers : question d’intégration - Bérengère Hurand (VertigO)
The circular economy model prevailing today in the West promises to replace the systematic elimination of the household wastes by their reprocessing, their recovery, and the exploitation of their energetic or material potential. A specialized industry is in charge to reduce their mass and at the same time, to supply the production chain with an available, abundant and renewable resource. So the useless waste becomes useful; it is no more an disused thing, but it starts his reintegration in the economy. But what about the politic integration? The waste industrial processing may be suspected of stopping it. The monopoly position of this technical system, which is effective in a large scale, seems indeed to have encouraged rather than reduced the wastes production. It seems also to have led to an erosion of the sense of responsibility of the users. A genuine wastes policy should free itself from the purely technical and economic matter of the problem, in order to think an other definition of waste than which gives the industry. It is for users to decide when the thing becomes waste. They shouldn’t behave like simple relay in the production / consumption chain, they must have the technical possibility and the political will for retain the things in the using sphere, before pass them on the industry which will make materials of it.